Perception of food quality in yams among Nigerian farmers - Otegbayo, B.; Kehinde, A.L; Sangoyomi, T.; Samuel, F.O.; Okonkwo, C. (2009)
This study is a qualitative investigation on the perception of food quality in yams by farmers from two yam growing communities with different cultural backgrounds but located in the savanna agroecological zone of Nigeria (Federal Capital Territory (FCT), Abuja and Okeogun area of Oyo State). Focus group discussion (FGD) was used to collect data from respondents who were mainly yam farmers and traders. Results showed that the food quality of yam food products by the farmers is based mainly on sustainable, derivable income from cultivating the species and the varieties of yam and on the sensorial quality of the yam product. The most important food product from yam in both areas studied was pounded yam while textural quality was the most important food quality attribute considered. Farmers do not have a means of predicting or perceiving or knowing the food quality of yam food products before processing but they use indigenous knowledge such as pattern of leaf foliage, and smoothness and shape of the tuber to identify species and varieties rather than predict food quality. In view of these findings extension work is needed in order to enlighten or encourage the farmers on what food quality is, and the need to gear their production towards planting for food quality (nutritional, commercial, industrial, and utilization) rather for subsistence use only.